(untitled) (European Journal of Formal Sciences and Engineering, 2021)
Most of the work on resilience of urban infrastructures focuses on their technical performance and reliability in disaster situations. In general, when we link urban infrastructure and Civil Engineering, we think of technology, engineering, constructions and technical or control buildings. In a state of pandemic like the current one, the study of the relationship between urban infrastructures and resilience is a phenomenon scarcely studied in the literature. The main objectives of the article are to analyse, from a Civil Engineering and actors’ perspective, the role and behaviour of urban infrastructures for the maintenance of the wellbeing of the community in a pandemic situation, and to fill a gap in the existing bibliography. The authors argue that the human factor is the most important element for infrastructure to be resilient in a Covid-19 situation. To achieve the objectives, a review of the literature was carried out considering the works published in the last 10 years. Then, a reflection is made about the influence of the resilience in infrastructures during a pandemic situation considering the relevant sustainability factors. As practical implications of this article, the drawn conclusions are expected to represent value for the societies of the future.